IEEE InternationalElectron Devices Meeting, 2005. IEDM Technical Digest.
DOI: 10.1109/iedm.2005.1609321
|View full text |Cite
|
Sign up to set email alerts
|

Electro-thermal transport in metallic single-wall carbon nanotubes for interconnect applications

Abstract: This work represents the first electro-thermal study of metallic single-wall carbon nanotubes (SWNTs) for interconnect applications. Experimental data and careful modeling reveal that self-heating is of significance in short (1 < L < 10 µm) nanotubes under high-bias. The low-bias resistance of micron scale SWNTs is also found to be affected by optical phonon absorption (a scattering mechanism previously neglected) above 250 K. We also explore length-dependent electrical breakdown of SWNTs in ambient air. Signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…An analytic expression for the temperature profile T(x) along the SWNT can first be obtained if we make the simplifying assumption of uniform heat generation along the tube, p' ≈ I 2 (R-R C )/L where R is the total electrical resistance of the nanotube and R C is the combined electrical resistance of the two contacts. This is reasonable, given the relatively flat expected temperature profiles, especially in longer tubes [17,21] and yields:…”
Section: Joule Heating and Breakdown In Airmentioning
confidence: 97%
See 3 more Smart Citations
“…An analytic expression for the temperature profile T(x) along the SWNT can first be obtained if we make the simplifying assumption of uniform heat generation along the tube, p' ≈ I 2 (R-R C )/L where R is the total electrical resistance of the nanotube and R C is the combined electrical resistance of the two contacts. This is reasonable, given the relatively flat expected temperature profiles, especially in longer tubes [17,21] and yields:…”
Section: Joule Heating and Breakdown In Airmentioning
confidence: 97%
“…3 above. Using the finite-element model described in the later sections of this work we have found that the breakdown voltage of SWNTs shorter than 1 µm is consistent with a contact thermal resistance R C,Th ≈ 5 × 10 6 K/W [11,21], however more detailed future efforts must be made to investigate electro-thermal transport in such short metallic SWNTs. In addition, we note that when the electrical resistance of the contacts (R C ) is significant, the breakdown voltage in Eq.…”
Section: Joule Heating and Breakdown In Airmentioning
confidence: 99%
See 2 more Smart Citations
“…This is much smaller than g ~ 100 mWK -1 m -1 estimated for tubes lying on solid SiO 2 substrates, 6 indicating little heat sinking by the gaseous molecules around the nanotube. The combined SWNT heat loss to the gas ambient and to radiation is estimated to be < 2 % of the power dissipation at all relevant temperatures.…”
mentioning
confidence: 84%